2000
DOI: 10.1055/s-2000-95
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Endoscopic Retrograde Cholangiopancreatography

Abstract: The importance of diagnostic endoscopic retrograde cholangiography (ERCP) has dramatically decreased owing to the development of less invasive techniques such as ultrasonography, computed tomography, endoscopic ultrasonography, and finally magnetic resonance cholangiopancreatography (MRCP). MRCP is becoming the gold standard in the diagnostic work-up of the pancreaticobiliary duct. However, MRCP cannot solve all the problems that occur, and still has inadequate resolution for small stones and tiny pancreatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…However, for tumors in the region of the papilla of Vater, it allows good visualization of the lesion and biopsy specimens to be taken. Sensitivity for differentiation between benign or malignant biliary strictures is about 90% with a specificity of only 70% [26][27][28]. However, ERC does not allow for complete staging of biliary tumors, since only the tumor extent within the biliary system is displayed, whereas the tumor itself and possible invasion of the vasculature, hepatic parenchyma or other surrounding tissue cannot be assessed.…”
Section: Imaging Techniques Of the Biliary Systemmentioning
confidence: 95%
“…However, for tumors in the region of the papilla of Vater, it allows good visualization of the lesion and biopsy specimens to be taken. Sensitivity for differentiation between benign or malignant biliary strictures is about 90% with a specificity of only 70% [26][27][28]. However, ERC does not allow for complete staging of biliary tumors, since only the tumor extent within the biliary system is displayed, whereas the tumor itself and possible invasion of the vasculature, hepatic parenchyma or other surrounding tissue cannot be assessed.…”
Section: Imaging Techniques Of the Biliary Systemmentioning
confidence: 95%
“…Although endoscopic biliary stenting is the main treatment for biliary obstruction, it can fail in 3 % ± 12 % of cases [9,10], at pres− ent leaving only surgical or percutaneous approaches as alterna− tives. However both have a higher morbidity and mortality, and permanent transhepatic external drainage may be uncomforta− ble for patients receiving palliative treatment.…”
mentioning
confidence: 99%
“…However, some authors have suggested that preoperative ERCP screening for CBD stones is inappropriate, not only because the cost is high but also because, for the majority of procedures, such screening is unnecessary. In addition, complications, such as pancreatitis, cholangitis, and drug side effects, were reported in 2% of patients who underwent ERCP 14…”
Section: Discussionmentioning
confidence: 99%